2022
DOI: 10.1051/e3sconf/202233600045
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of spray deposited nickel oxide (NiO) thin film in Alkaline electrolyte

Abstract: Nickel oxide (NiO) Thin film was successfully deposited on the glass substrate using an inexpensive spray pyrolysis (SP) technique. The structural, morphological, and optical properties have been studied, thus the electrochemical behavior of NiO film in Alkaline electrolytes has been investigated. The X-ray diffraction (XRD) analysis showed that NiO thin film exhibit a polycrystalline cubic rock-salt structure with a preferential orientation on the plane (111). This result was confirmed using Raman spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The improved CE in 0.4 lm is attributed to the porous and crystalline structure of NiO, providing an effective interface with the electrolyte. 31 In general, EC materials with an amorphous nature are expected to provide high CE. 73 However, the NiO lms with a good polycrystalline nature in the present work showed superior CE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved CE in 0.4 lm is attributed to the porous and crystalline structure of NiO, providing an effective interface with the electrolyte. 31 In general, EC materials with an amorphous nature are expected to provide high CE. 73 However, the NiO lms with a good polycrystalline nature in the present work showed superior CE.…”
Section: Resultsmentioning
confidence: 99%
“…30 Doping of certain elements can also bring enhancement in EC properties. For example, Brioual et al 31 have reported that an increment in the optical modulation, from 27 to 38%, of a 120 nm lm was possible by doping with 2 at% In. There are also other examples of anodic NiO in the literature (see Table 1).…”
Section: Introductionmentioning
confidence: 99%